Rancang Bangun Frontend E-Katalog Responsive Menggunakan Bootstrap (Information Technology and Telematics, 2015)
E-Catalog frontend application responsive using boostrap. The problem is how to create a comfortable displays for user in both desktop and smartphone. So this application could adjust the users in accesing this e-catalog. This research has resulted responsively e-catalog display using bootstrap based on UD.Sumber Berkah Furniture’s e-catalog. This e-catalog could be used for media promotion of furniture products to customers. Another goal of this e-catalog is UD.Sumber Berkah Furniture might get more customers by user interface furniture products in e-catalog furniture. The further improvment is adding order menu on the next plan e-catalog. Keywords: E-Catalog, Bootstrap, PHP, MySQL